Learning environments to develop vocational excellence - James Relly, S; Holmes, C; Mayhew, K (Centre on Skills, Knowledge and Organisational Performance, 2012)
WorldSkills UK, under the auspices of Find a Future, selects and prepares young people, mostly aged 18-22, to compete in the World Skills Competition. Prior to competition, these young people have developed a range of skills and knowledge in their chosen field through coursework and/or workplace experience. Potential competitors, either from Further Education or university, or in employment as apprentices or employees, build upon this prior experience when competing in numerous regional and national skill competitions held throughout the UK. It is these competitions that form the building blocks for selection into Team UK. This research focuses specifically on how the learning and working environment experienced by WorldSkills UK participants can affect team selection and potential success at WSC. It addresses three key questions:  What are the features of the learning environments for WorldSkills UK participants and non- participants?  Do these differ for squad and team members? Or for WorldSkills UK participants versus non- participants?  Are these features related to performance at the WSC? The results presented in this report are based on 474 survey responses. We surveyed 114 team members, 167 squad members, 114 young people who were not selected for the squad (Non- squad), 51 young people not involved in WorldSkills (Non-WS) and 28 employers from across the 2009, 2011, 2013 and 2015 WSC. Using statistical analysis, the survey responses are compared across these groups and in seven different areas: participation in and understanding of the work environment; task performance; learning resources and access; judgement, decision-making, problem solving and reflection; experience, task transition and career progression; learner status, worker status and formalisation; and organisational development. Overall the findings show that aspects of the seven areas work together to help the young person develop their skills and knowledge to a high level for these workplaces – no one area is more significant than another – and there are strong sectoral/skill cluster distinctions with regards to the work environment and the types of tasks performed at work.